Pattern of Antimicrobial Prescription and its Cost Analysis in Respiratory Tract Infection - Dawadi, Sushma; Rao, B.S.; Khan, G.M. (Kathmandu University Journal of Science, Engineering and Technology, 2005)
Many reports from different parts of the world show that antimicrobials are used both widely and often indiscriminately. Indiscriminate usage could increase the cost of therapy, incidence of adverse drug reaction, and increase in the rate of emergence of bacterial resistance. There is evidence to show that antimicrobials are widely used in Nepal. This study relates to the drug prescribed treatment of Respiratory Tract Infection (RTI), which is a cause of morbidity and mortality in children and adults. This problem is important considering climate, geographical and living condition of the people. Out of total 190 patients 20% were diagnosed as having Upper Respiratory tract infection (URTI), 48.43% had Lower Respiratory Tract Infection (LRTI) and 31.57% as having chronic obstructive pulmonary disease (COPD) or asthma. 42.1% were male patients and 57.89% were females. Among the six different antimicrobials prescribed the most commonly used therapeutic group were penicillin’s (47.36%) followed by tetracycline (43.15%), macrolides (4.2%), quinlones (3.1%) and cephalosporins (2.1%) .14.56% of the drug was prescribed using generic name and the remaining 85.43% of the drugs were prescribed using brand name. It was found that the Maximum and minimum price of antimicrobial regimen in two hospitals were same although slight difference in brands available was observed. The cheapest antimicrobial regimen in RTI treatment was Doxycycline, 100 mg once daily for 10 days and the most expensive was cefixime 400 mg for 7 days. The cost of the same drug varied according to the brands.